Utilization of Terra-MODIS Satellites for Phenomenon Analysis Urban Heat Island in Kalimantan Island (EarthCare, 2022)
Urban development on the island of Kalimantan in various aspects can in principle increase productivity through the expansion of built-up land. This can have an impact on increasing temperatures in urban areas and lower temperatures around them. This phenomenon is known as urban heat island (UHI). For this reason, it is essential to analyze the phenomenon. The UHI analysis in this study utilizes remote sensing technology using the Terra-MODIS satellite. Terra-MODIS satellite imagery is used to determine land surface temperature (LST) and normalized difference vegetation index (NDVI). The urban areas that are the object of analysis are Pontianak City and Balikpapan. The data used is imagery data from 2001 to 2020. In the province, ESG and NDVI are inversely proportional, but in this study, a condition was produced where the situation was directly proportional. This condition shows that in the analysis of the UHI phenomenon, other factors are needed besides these two parameters, such as humidity and precipitation.